Evaluation study of mathematics education master program curriculum - Putu Suharta (Universitas Pendidikan Ganesha, 2018)
Curriculum is a very important component in implementing various programs. Therefore, it should be developed with the principles of relevance, effectiveness, efficiency, continuity, and flexibility. The objective of this research is to explore the incompatibility and compatibility of the Mathematics Education Master Program Curriculum with existing standards. This type of research is qualitative with evaluation method. Documents, alumni, students, and stakeholders (principal, head of university, head of Youth and Sports Office) are the sources of data used in this study. Data are collected using documentation study method, questionnaire, focus group discussion, with document filling form instrument, questionnaire, and record form. Research data is analyzed descriptively. The results of the research are: (1) Context, Input, Process, and Product models can be used to analyze the curriculum incompatibility that is implemented with existing standards or guidelines, (2) there is incompatibility between the courses given with the profile of graduates as a researcher, and the learning process is conducted with the characteristics of the learning process according to National Standards of Higher Education (NSHE), and (3) there is compatibility between: the courses given with the profile of educators and professionals; profile of graduatess with level 8 of the National Qualification Framework of Indonesian (NQFI); lecturers’ condition, the micro-level curriculum, facilities and infrastructures, and the number of students with the existing standards; and quality of graduates from aspect of Grade Point Average (GPA), study period, waiting period, and graduate performance with expectation